Novel TLR 7/8 agonists for improving NK cell mediated antibody-dependent cellular cytotoxicity (ADCC) - Vidhi Khanna (Nature Portfolio, 2021)
Abstract There is a significant interest in designing therapeutic agents that can enhance ADCC and thereby improve clinical responses with approved antibodies. We recently reported the combination of an imidazoquinoline-based TLR7/8 agonist (522) with a monoclonal antibody improved ADCC in vitro and in vivo. In the present study, we tested several new small molecule TLR7/8 agonists that induce significantly higher cytokines compared to both the FDA-approved TLR7 agonist, imiquimod, and 522. We evaluated these agonists in combination with monoclonal antibody therapy, with the main goal of enhancing ADCC. Our studies show these TLR7/8 agonists induce robust pro-inflammatory cytokine secretion and activate NK cells. Specifically, we found the agonists 574 and 558 significantly enhanced NK cell-mediated ADCC in vitro as well as enhanced the anti-cancer efficacy of monoclonal antibodies in two different in vivo mouse models. Additionally, we found the agonists were able to stimulate CD8 T cells, likely indicative of an early adaptive immune response.